Bush Snapbean Production in Miami-Dade County, Florida - Shouan Zhang; Dakshina Seal; Monica Ozores-Hampton; Mary Lamberts; Yuncong Li; Waldemar Klassen; Teresa Olczyk (EDIS)
Miami-Dade County is the primary production region for fresh-market bush snapbeans with 57% or 18,696 acres of the Florida bean acreage. Production costs vary from $16.53 to $21.87 per 30 lb. bushel or $4,046 to $4,711 per acre. Acceptable yields range from 185 to over 300 bushels per acre. Snapbeans produced in Miami-Dade County are sold nationwide for the fresh market starting just before Thanksgiving and continuing through the winter and spring months. This revised 9-page fact sheet was written by S. Zhang, D. Seal, M. Ozores-Hampton, M. Lamberts, Y. Li, W. Klassen, and T. Olczyk, specifically for growers in Miami-Dade County as a supplement to The Vegetable Production Handbook for Florida (SP170). Published by the UF Department of Horticultural Sciences, July 2014.